La guerre vue d’en haut - Sylvain Le Cloërec (Conserveries Mémorielles)
A majority of historical video games deals about World War II. It appears that war takes a major place instead of some social aspects of the conflict, as in Hearts of Iron IV. In this wargame, the player sees the war from above and the gameplay focus on military production and research while putting aside many great aspects of the war.